2007
DOI: 10.1159/000103375
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial Cyclic Stretch-Stimulated Glucose Transport Is Mediated by a Ca<sup>2+</sup>-Dependent Mechanism in Cultured Skeletal Muscle Cells

Abstract: Objective: Mechanical stimuli such as stretch increase glucose transport and glycogen metabolism in skeletal muscle. However, the molecular mechanisms involved in the mechanotransduction events are poorly understood. The present study was conducted in order to determine whether the signaling mechanism leading to mechanical stretch-stimulated glucose transport is similar to, or distinct from, the signaling mechanisms leading to insulin- and contraction-stimulated glucose transport in cultured muscle cells. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 102 publications
(78 reference statements)
2
31
0
Order By: Relevance
“…As such, this adaptive phase allows for a more coordinated distribution of blood flow to deliver more blood flow to metabolically active sites. Furthermore, it has also been shown that skeletal muscle hypoxia (reduced O 2 ) and/or passive stretch can increase glucose transport and translocation of glucose transporters (Cartee et al ., ; Iwata et al ., ). Additional evidence reveals that following exercise, elevations in glucose uptake and glycogen repletion follow a similar time course as that of skeletal muscle blood flow (Ivy, ).…”
Section: Discussionmentioning
confidence: 97%
“…As such, this adaptive phase allows for a more coordinated distribution of blood flow to deliver more blood flow to metabolically active sites. Furthermore, it has also been shown that skeletal muscle hypoxia (reduced O 2 ) and/or passive stretch can increase glucose transport and translocation of glucose transporters (Cartee et al ., ; Iwata et al ., ). Additional evidence reveals that following exercise, elevations in glucose uptake and glycogen repletion follow a similar time course as that of skeletal muscle blood flow (Ivy, ).…”
Section: Discussionmentioning
confidence: 97%
“…Recent work by Rose and colleagues clarified this mechanism by demonstrating that the suppression of protein synthesis by contraction was partially dependent upon Ca 2+ ‐dependent activation of eEF2K (Rose et al 2009). However, Ca 2+ influx is not specific to contraction: stretch‐induced 2‐deoxyglucose uptake in C2C12 myotubes is prevented by the ryanodine receptor 1 (RyR1) inhibitor dantrolene and stretch of myotubes increases Ca 2+ influx via mechanically sensitive plasma membrane ion channels suggesting that both sarcoplasmic reticulum and extracellular derived Ca 2+ are increased with stretch (Nakamura et al 2001; Iwata et al 2007). Therefore we wondered if stretch‐induced Ca 2+ currents could induce eEF2K activity and thereby stimulate inhibitory phosphorylation of eEF2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, application of cyclic strain to primary human myoblasts enhanced elasticity, myofiber diameter and area when compared to static culture conditions [25]. Similarly, enhanced metabolic activity of C2C12 mouse myoblasts were observed in response to 10% cyclic stretch [31] and, conversely, cessation of 12% stretch on C2C12 cultures caused myotube atrophy [32]. Thus, we hypothesized that biophysical cues (cyclic uniaxial strain) in conjunction with biochemical stimuli (azacytidine) would induce ASCs to exhibit enhanced myogenic outcomes (alignment, multi-nucleation, and expression of muscle-specific proteins) and significantly improve the efficiency of differentiation.…”
Section: Introductionmentioning
confidence: 99%